الإشكاليات القانونية حول اختصاص المحكمة الدستورية الكويتية في الفصل بالطعون الإنتخابية - الكندري، أحمد عادل (جامعة الكويت - مجلس النشر العلمي, 2022)
تملك المحكمة الدستورية اختصاصين متعلقين بالفصل في الطعون الدستورية واختصاصا آخر متعلقا بالفصل في الطعون الانتخابية وصحة العضوية. ينصب البحث على الاختصاص الأخير للمحكمة سعيا لبيان الإشكالات والوقوف عليها لإيجاد الحلول. فالغاية من إنشاء المحكمة الدستورية، هو الوقوف على دستورية القوانين والمراسيم واللوائح حفاظا على الشرعية الدستورية وهو ما كان جليا في نص المادة 173 من الدستور الكويتي. كما أن الاختصاص المتعلق بالفصل في الطعون الانتخابية هو اختصاص استئثاري نجم عنه العديد من الإشكالات في الواقع العملي، تلك التي أدت إلى تضارب في الأحكام وهدر الحجية وفقدان الشعور بالأمان القانوني؛ مما يوجب التصدي لهذه الإشكاليات، وصولا إلى اقتراح مشروع قانون شامل يتفادى جميع الإشكالات محل الدراسة. The Constitutional Court has two jurisdictions related to the adjudication of constitutional appeals and another jurisdiction related to the adjudication of electoral appeals and the validity of membership. The research focuses on the final jurisdiction of the court in an effort to clarify the problems and identify them to find solutions. The purpose of establishing the Constitutional Court is to examine the constitutionality of laws, decrees and regulations in order to preserve constitutional legitimacy, which was evident in the text of Article 173 of the Kuwaiti Constitution. In addition, the jurisdiction related to the adjudication of electoral appeals is an exclusive jurisdiction, which has resulted in many problems in practice, which have led to conflicting judgments, wasting authenticity and losing a sense of legal security; which necessitates addressing these problems, leading to the proposal of a comprehensive draft law that avoids all the problems under study.
Keywords: المحكمة الدستورية -- الطعون الانتخابية -- الاختصاصات القضائية -- الكويت